The challenge of a late diagnosis of Autism Spectrum Disorder: co-occurring trajectories and camouflage tendencies. a case report of a young Autistic female with Avoidant Restrictive Food Intake Disorder - Sara Passarini; Sara Passarini; Silvia Guerrera; Maria Picilli; Maria Picilli; Elisa Fucà; Laura Casula; Deny Menghini; Sabine Pirchio; Valeria Zanna; Giovanni Valeri; Stefano Vicari; et al. (Frontiers in Psychiatry)
IntroductionAutistic individuals may show several psychiatric co-occurrences, including Feeding and Eating Disorders (FEDs). Avoidant and Restrictive Food Intake Disorder (ARFID) consists of avoidance or restriction in food intake, leading to significant weight loss, nutritional deficiencies, and marked interference with psychosocial functioning. Both Autism Spectrum Disorder (ASD) and ARFID are characterized by the two main features of cognitive rigidity and sensory sensitivity, which may complicate differential diagnosis. There is a notable lack of information on the manifestation of ASD-ARFID co-occurrence, as well as tailored assessment tools and practice, and therapeutic approaches.Case descriptionThis report provides a detailed description of L., a young girl with a late diagnosis of ASD who also developed unspecific depressive mood disorder and ARFID in co-occurrence. After the diagnosis of ASD, L. underwent multiple evaluations to address emerging psychiatric co-occurrences and symptom exacerbation, and in order to develop the most effective integrated treatment.ConclusionThe case of L. expands the knowledge on the phenotype of Autistic females and exemplifies how delayed diagnosis may exacerbate functioning differences and increase the camouflage phenomenon. Additionally, it underscores the importance of improving tailored evaluation, combined treatment plans, with both cognitive-behavioral therapy and drugs, and monitoring the evolving patterns of Autistic manifestations and associated psychiatric co-occurrences.